Effect of the incorporation of Neem (Azadirachta indica) wood ash in Kodeck ceramic materials for the manufacture of fired bricks (Far-North Cameroon) - Soureiyatou Fadil-Djenabou; Paul-Désiré Ndjigui; Nenita Bukalo; George I. Ekosse (Heliyon, 2023)
The current study evaluates the suitability of Neem (Azadirachta Indica) wood ash as raw material in the production of ceramic bricks for their application in construction. Accordingly, for the fabrication of bricks, compositions were prepared by adding increasing amounts of Neem wood ash (0%, 5%, and 10% in wt.). The specimens were manufactured by mixing clay with a Neem wood ash amendment and subsequently compacted and fired at 850 °C, 950 °C, and 1050 °C. The fired samples were characterized to determine their technological properties. The results indicate that brick formulations containing Neem wood ash decreased the bulk density up to 8%. Water absorption increased up to 10% and porosity also increased up to 20% with wood of ash. These values meet the Turkish TS EN standards for masonry structures. Due to the interesting performances observed, the potential used up to 10 wt% of Neem Wood ash in ceramic formulations of industrial interest was confirmed. Therefore, incorporating ash into a clay material reduces environmental problems and the total cost of raw material disposition. This is very important in the Sahelian zone and it provides a great opportunity for the inhabitants of this zone.